Depresión y autoestima en adultos mayores institucionalizados y no institucionalizados en la ciudad de Lima - Orosco Goicochea, Carlos Javier (2015)
The present study aimed at comparing levels of depression and self-esteem among institutionalized and non institutionalized senior citizens. The respondents were 40 institutionalized and 45 non-institutionalized senior citizens both from the upper middleclass, and over 60 years of age. Both groups were given the Beck Depression Inventory (BDI) and the Coopersmith Self-Esteem Inventories-Adult form (CSEI). Results show that there is a significant and inverse correlation between depression and self-esteem. Additionally, both groups showed similar results on regarding levels of depression and self-esteem.